Edge Waves and Localization in Lattices Containing Tilted Resonators - Tallarico, Domenico; Trevisan, Alessio; Movchan, Natalia V.; Movchan, Alexander B. (Frontiers in Materials, 2017)
The paper presents the study of waves in a structured geometrically chiral solid. A special attention is given to the analysis of the Bloch-Floquet waves in a doubly periodic high-contrast lattice containing tilted resonators. Dirac-like dispersion of Bloch waves in the structure is identified, studied and applied to wave-guiding and wave-defect interaction problems. The work is extended to the transmission problems and models of fracture, where localisation and edge waves occur. The theoretical derivations are accompanied with numerical simulations and illustrations.